Drug-related bullous fixed pigmented erythema related to the use of ivermectin in a patient with SARS-Cov2 pneumonia: Case Report - Aguilar-Urbina, Edi William (2021)
Background: Bullous fixed pigmented erythema is a potentially serious form of toxicoderma. It is characterized by the appearance of cutaneous and / or mucosal lesions, single or multiple, which can appear in any area, after the administration of a drug or other substance. A 73-year-old man is presented with a diagnosis of bullous fixed pigmented erythema secondary to the ingestion of ivermectin. It is necessary for the physician to recognize the adverse effects of self-medication with ivermectin against SARS CoV-2, to make an early diagnosis and initiate timely treatment.